2019
DOI: 10.1029/2018jd030001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anthropogenic Emission Injection Height Uncertainty on Global Sulfur Dioxide and Aerosol Distribution

Abstract: Anthropogenic sulfur compounds play an important role in acid deposition, aerosol particle formation, and subsequent radiative forcing and human fine particulate exposure. There are substantial uncertainties in processes influencing sulfate and precursor distributions, however, that have not yet been resolved through comparisons with observations. We find here an underappreciated factor that has a large impact on model results: uncertain emission height. Global aerosol‐climate model simulations indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…S3 that observed MDA8 ozone concentrations in many cities can shift by more than 60 ppbv in 2 d. Such variations, however, are challenging for Eulerian chemical models to capture due to numerical diffusion, even at 10 km grid resolution, and representative issues when comparing gridded simulated results to observations at urban sites (Young et al, 2018). Artificial mixing of ozone precursors in model grids may cause higher ozone production efficiency and therefore positive ozone biases (Wild and Prather, 2006;Yu et al, 2016;Young et al, 2018). In addition, models have limited skills in presenting local emissions and meteorological conditions, particularly over complex terrain (e.g., in WCH and SCB cities) Ni et al, 2018).…”
Section: Model Configurationsmentioning
confidence: 98%
“…S3 that observed MDA8 ozone concentrations in many cities can shift by more than 60 ppbv in 2 d. Such variations, however, are challenging for Eulerian chemical models to capture due to numerical diffusion, even at 10 km grid resolution, and representative issues when comparing gridded simulated results to observations at urban sites (Young et al, 2018). Artificial mixing of ozone precursors in model grids may cause higher ozone production efficiency and therefore positive ozone biases (Wild and Prather, 2006;Yu et al, 2016;Young et al, 2018). In addition, models have limited skills in presenting local emissions and meteorological conditions, particularly over complex terrain (e.g., in WCH and SCB cities) Ni et al, 2018).…”
Section: Model Configurationsmentioning
confidence: 98%
“…F. Wang et al, 2014;Chen et al, 2015;Geng et al, 2015;Li et al, 2015;Xie et al, 2015;Zhang and Cao, 2015;Chen et al, 2016). Moreover, modeling analysis can help understand the chemical and physical processes affecting aerosol formation and evolution (e.g., Ying et al, 2009;Zhang et al, 2010;Liao et al, 2014;Cheng et al, 2016;Yang et al, 2016;Zhao et al, 2017). Yang et al (2016) reproduced an increasing trend of winter PM 2.5 concentrations averaged over East China for 1985China for -2005 with the GEOS-Chem model and found that the variations in anthropogenic emissions dominated the increase in winter surface PM 2.5 concentrations over East China, and the variations in meteorological fields also played an important role in influencing the decadal increase in winter PM 2.5 concentrations over East China.…”
Section: Introductionmentioning
confidence: 99%
“…For meteorology, we will focus on the PBL mixing process that has been found to largely control the diurnal variation of surface pollutant concentrations (M. . For emissions, based on the findings of Wang et al (2010) and Yang et al (2019), the diurnal variation and injection height of emission will be investigated. The rest of the paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in aerosols over Europe was mainly attributed to continuous reductions in local European anthropogenic emissions of aerosols and precursor gases since the 1980s (Smith et al, 2011), which are a result of legislation for improving air quality. In addition to local emissions, aerosol levels can also be affected by aerosol transport at continental scales (Zhang et al, 2017;Yang et al, 2018a). Aerosol emissions in major economic regions of the world have been changing rapidly during the past few decades owing to economic development and environmental measures.…”
Section: Introductionmentioning
confidence: 99%